Novel method for stress history analysis in normally consolidated clays (2021)
The historical investigation of stresses in a clay material is essential to predict the compressible behaviour of a soil layer that, in most cases functions as a foundation support of superstructures. Because the stresses underwent in the geological past provide useful information to understand the response of the soil today. There are numerous methods for the interpretation of the preconsolidation stress, defined by the standard unidimensional consolidation test. The concept of preconsolidation stress is extremely useful in the geotechnical field to analyze and estimate settlements in a clay deposit, in addition to normalizing other parameters for comparative purposes. Through mineralogical analysis and consolidation tests based on different models for the estimation of the vertical consolidation coefficient, preconsolidation stress is evaluated by applying disparate constitutive methods. In order to observe the dispersion of results for a particular soil. A new technique is proposed for the determination of the preconsolidation stress prescribed in differential terms and with a high degree of objective interpretation.